RATE OF FILTRATION BY Perna viridis PRE-EXPOSED TO HEAVY METALS - PRABHUDEVA, K N; MENON, N R (Fishery Technology, 2017)
Perna viridis exposed to different concentrations of copper and zinc for varying periods and then the rate of filtration estimated under metal free culture conditions. The concentrations under which the animals were maintained before the experiments were 0.025 to 0.150 p.p.m. of zinc and 0.005 to 0.08 p.p.m. of copper.